Migrant Workers Electrocuted, Decapitated, and Falling to Death at Workplaces - Human Rights Watch (Human Rights Watch, 2025)
Scores of migrant workers in Saudi Arabia die in gruesome yet avoidable workplace-related accidents, including falling from buildings, electrocution, and even decapitation